Synthesized Phosphonium Compounds Demonstrate Resistant Modulatory and Antibiofilm Formation Activities against Some Pathogenic Bacteria - Cedric Dzidzor Kodjo Amengor; Cynthia Amaning Danquah; Emmanuel Bentil Asare Adusei; Francis Klenam Kekessie; Francis Ofosu-Koranteng; Paul Peprah; Benjamin Kingsley Harley; Emmanuel Orman; Joseph Adu; Yussif Saaka (Heteroatom Chemistry)
A library of six compounds with new hybrids in a single molecule triazole ring attached to the phosphonium salts was synthesized. Click chemistry was, however, used to synthesize the 1-, 2-, and 3-triazole intermediates as a tether for the hybrid phosphonium salts. Their antibacterial activity against Gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis), Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa), and Mycobacterium smegmatis mc2155 was determined using the HT-SPOTi assay. Compound 2 showed the most effective antimicrobial activity as it inhibited the growth of Pseudomonas aeruginosa and Staphylococcus aureus at 0.0125 µg/mL and 31.25 µg/mL, respectively. From the FICI data, compounds 2ET-TOL (2) and RABYL-TOL (4) successfully modulated the activities of amoxicillin against Pseudomonas aeruginosa and Staphylococcus aureus. All the test compounds exhibited a concentration-dependent biofilm formation inhibition against S. aureus, except P-Z (compound 6). Compounds P-MEOXY (1) and 2ET-TOL (2) exhibited mild activity against P. aeruginosa with compound 4 showing antimycobacterial activity at 500 µg/mL.